2018 Physics Education Research Conference Proceedings 2019
DOI: 10.1119/perc.2018.pr.strzys
|View full text |Cite
|
Sign up to set email alerts
|

Smartglasses in STEM laboratory courses – the augmented thermal flux experiment

Abstract: Augmented reality (AR) learning scenarios with see-through smartglasses create a wearable education technology providing active access to various additional information without distracting from the physical interaction with reality. We already have introduced such an AR version of a standard physics experiment of introductory lab courses on heat conduction in metals, using real physical data from external sensors for analyzing and displaying thermal phenomena in real-time. Besides a direct feedback, ensuring t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Less distal and more sensitive performance measures would have possibly made learning gains more visible and emphasized the effects of AR. Moreover, the developed AR application could also be used with smartglasses, potentially leading to more pronounced effects compared to tablet‐based AR and non‐AR conditions (Strzys et al ., ; Thees et al ., under review). Smartglass applications render the learners' hands free for experimentation, which could foster embodied learning (Korbach, Ginns, Brünken, & Park, accepted) and reduce interruptions, caused by tablet use, leading to more temporal contiguity of corresponding information.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Less distal and more sensitive performance measures would have possibly made learning gains more visible and emphasized the effects of AR. Moreover, the developed AR application could also be used with smartglasses, potentially leading to more pronounced effects compared to tablet‐based AR and non‐AR conditions (Strzys et al ., ; Thees et al ., under review). Smartglass applications render the learners' hands free for experimentation, which could foster embodied learning (Korbach, Ginns, Brünken, & Park, accepted) and reduce interruptions, caused by tablet use, leading to more temporal contiguity of corresponding information.…”
Section: Discussionmentioning
confidence: 99%
“…The two conditions were contrasted for changes in conceptual knowledge and perceived cognitive load. Due to their broad acceptance and availability, tablet PCs were used as displaying technology instead of smartglasses, which have also proven useful for this type of application (Kuhn et al ., ; Strzys et al ., , ; Thees et al ., under review).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on this approach, through AR it is attempted to combine the best of two worlds: situated active learning in a meaningful real-world environment and virtual learning environments carefully designed according to the principles of the Cognitive Theory of Multimedia Learning [ 12 ]. Initial studies indicate that through fulfilling the spatial contiguity principle, AR-based learning environments can reduce cognitive load [ 13 , 14 ] and increase learning gains [ 15 ]. Moreover, Szajna et al [ 16 ] found that HMD-AR-based applications for training can significantly reduce the time required to perform tasks.…”
Section: Introductionmentioning
confidence: 99%